Estudio de Viabilidad para la creación de centro de acopio para pequeños productores de productos a base de hoja de coca en el municipio de Argelia Cauca. - Romero Hoyos, Danna Valentina (Universidad Antonio Nariño, 2023)
Through this research, the feasibility of creating a collection center for coca-based products in the municipality of Argelia Cauca is identified. A place that has been called the red zone, due to the constant confrontations between armed groups and the lack that they live as a consequence of the abandonment of the state. Unleashing a problem that they no longer have to support their needs, as they have done for many years. There are no guarantees on this natural resource anymore